Mental Illness Causing Devalued Economic Output in any Given Context in the World: Exploring the Remedies - Tanima Chatterjee; Moh. Agus Sifa'; R.P. Banerjee (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
Economic output is a combination of the means of activities and the human intervention towards effective utilization of the means of the work. Human interventions are not merely random. It has a strong basis of individual and collective mental conditions depending on the different psychophysical and psycho-spiritual level. Mental illness has a direct impact on the motivation for thoughts and works. Usually ill mind lacks in the illumination of the cosmic goodness and thus becomes a prey to various factors of retardation in the field of work and thought. The present study identifies the relation between physical or intellectual output of an individual contributing to the economic development and sustainability, assesses on an important scale the psychophysical and psycho-spiritual context of individual, impacting economic activities and identifies the remedies to overcome mental illness to enhance individual output in order to get a better economic development and sustainable conditions. Findings suggests human dimensions including physical, intellectual and behavioral intervention are having direct relationship with economic growth in both micro and macro level. Individual’s position in psychophysical and psycho-spiritual model is being assessed through Maslow’s need hierarchy model and model of five different sheaths (Pancha Kosha) of consciousness and it has been observed that the economic output has direct relation with the position of individual in different levels of Maslow’s need hierarchy model and transcendental impact of Pancha Kosha on individual potential leading towards better output of an individual and therefore enhancing economic activity in the macro level. This study has also suggested certain remedies to enhance individual output through enhancing human potential in order to impact economic growth and sustainability in a positive manner.